Toponimia andina: problemas y métodos - Cerrón-Palomino, Rodolfo (2015)
While the interdisciplinary nature of the toponymy leads to a practice in which different disciplines are involved, one should not ignore the essential role of linguistics, the central role of it or what it should have in the proper toponymic scientific studies. This paper highlights the key role of linguistics within the interdisciplinary character of the toponymy, particularly in the Andean region, while offering a state of affairs, as well as constant examples of the kinds of problems or difficulties it faces toponymic analysis and their respective discipline backed resolution. Thus, to avoid reductionist and simplistic practice in the study of toponymy, an interdisciplinary methodology is proposed, but above all, aware of the need for a linguistic focus on the Andean region scientific studies.